CCDC134 facilitates T cell activation through the regulation of early T cell receptor signaling - Zhang, Tianzhuo; Shi, Qianwen; Gu, Huining; Yu, Biaoyi; Yin, Sha; Ge, Qing; Mo, Xiaoning; Liu, Xiaofeng; Huang, Jing (Frontiers in Immunology, 2023)
Modulation of surface T cell antigen receptor (TCR) expression is crucial for proper T cell development and maintenance of mature T cell function at steady state and upon stimulation. We previously determined that CCDC134 (coiled-coil domain containing 134), a cytokine-like molecule that served as a potential member of the γc cytokine family, contributes to antitumor responses by augmenting CD8+ T cell-mediated immunity. Here we show that T cell-specific deletion of Ccdc134 decreased peripheral mature CD4+ and CD8+ T cells, which resulted in impaired T cell homeostasis. Moreover, Ccdc134-deficient T cells exhibited an attenuated response to TCR stimulation in vitro, showing lower activation and proliferative capacity. This was further reflected in vivo, rendering mice refractory to T cell-mediated inflammatory and antitumor responses. More importantly, CCDC134 is associated with TCR signaling components, including CD3ϵ, and attenuated TCR signaling in Ccdc134-deficient T cells via altered CD3ϵ ubiquitination and degradation. Taken together, these findings suggest a role for CCDC134 as a positive regulator of TCR-proximal signaling and provide insight into the cell-intrinsic functional consequences of Ccdc134 deficiency in the attenuation of T cell-mediated inflammatory and antitumor responses.